Type 1 diabetes recurrence after SARS‐CoV‐2 infection in a subject with pancreas transplantation - Valentina Popolla; Alessandro Rizzi; Linda Tartaglione; Alfredo Pontecorvi; Dario Pitocco (Endocrinology, Diabetes & Metabolism, 2023)
Abstract Background During COVID‐19 pandemic, several studies have demonstrated a strong link between SARS‐CoV‐2 infection and diabetes mellitus. Hyperglycaemia is a frequent event during the infection, also in patients without a history of diabetes. Furthermore, several cases of diabetic ketoacidosis during COVID‐19 disease have been described. No data are available about the effects of SARS‐CoV‐2 infection on glycaemic control in pancreas transplant patients. Case presentation A 45‐year‐old woman affected by type 1 diabetes mellitus was treated with kidney‐pancreas transplantation in 2015, 6 years before COVID‐19 infection. After transplantation, insulin therapy was stopped with a good glycaemic control during the following years.After SARS‐CoV‐2 infection, she developed severe hyperglycaemia requiring insulin therapy again. During the acute phase of the infection, the detection of antibodies against islet cells (ICA) and against glutamic acid decarboxylase (GAD) was found positive. Conclusions The onset of hyperglycaemia after SARS‐CoV‐2 infection might be the result of a direct virus‐induced toxicity or the effect of a virus‐mediated activation of autoimmunity.